2000
DOI: 10.1046/j.1365-2036.2000.00752.x
|View full text |Cite
|
Sign up to set email alerts
|

Cure of Helicobacter pylori infection in atrophic body gastritis patients does not improve mucosal atrophy but reduces hypergastrinemia and its related effects on body ECL‐cell hyperplasia

Abstract: Cure of H. pylori infection in patients with atrophic gastritis reverses some adverse effects on gastric function and ECL cell hyperplasia. H. pylori infection may be cured in atrophic body gastritis patients with partial reversion of its negative consequences on acid secretion and body ECL cell hyperplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
96
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(106 citation statements)
references
References 35 publications
8
96
2
Order By: Relevance
“…The most common autoantibodies in H. pylori-infected patients are anticanalicular and appear to be directed against the Hϩ,K ϩ -ATPase (as are the classic anti-parietal cell antibodies) and are strongly associated with body atrophy. When H. pylori organisms are present along with AG, then treatment of the H. pylori infection is important and can even reduce the serum gastrin levels and cause regression of the ECL cell hyperplasia, though the atrophic changes do not appear to improve (24).…”
Section: Discussionmentioning
confidence: 99%
“…The most common autoantibodies in H. pylori-infected patients are anticanalicular and appear to be directed against the Hϩ,K ϩ -ATPase (as are the classic anti-parietal cell antibodies) and are strongly associated with body atrophy. When H. pylori organisms are present along with AG, then treatment of the H. pylori infection is important and can even reduce the serum gastrin levels and cause regression of the ECL cell hyperplasia, though the atrophic changes do not appear to improve (24).…”
Section: Discussionmentioning
confidence: 99%
“…For this purpose, systematic sampling of the gastric mucosa, including four biopsies from the antrum and seven from the fundus ⁄ corpus, was carried out. 10,17 The absence of H. pylori at histology or a decrease of at least 50% in the initial titre of H. pylori immunoglobulin G, associated with a reduction in inflammatory cells, was accepted as a criterion for the successful cure of infection. 19 Acid secretory tests were repeated, and fasting gastrin and pepsinogen I levels were also assessed.…”
Section: Study Design (Figure 1)mentioning
confidence: 99%
“…6 In 50% of patients with atrophic body gastritis, evidence of H. pylori infection, detected only at the serological level, has been found. 7 We and others have shown that, following the cure of H. pylori infection in patients with atrophic body gastritis, achlorhydria is partially reversed and histological corporal inflammation is improved; [8][9][10][11] however, it is still a matter of debate whether, following the cure of…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the same way, other randomized studies identified that H. pylori eradication in intestinal metaplasia could be important in the regression of this precancerous lesion [76,[109][110][111]119,120]. Oppositely, other trials, both follow-up and randomized control, had not identified regression of intestinal metaplasia when H. pylori eradication was administrated [121][122][123][124][125][126][127][128][129].…”
Section: Discussionmentioning
confidence: 96%